Ixazomib, lenalidomide, and dexamethasone is effective and well tolerated in multiply relapsed (≥2nd relapse) refractory myeloma: a multicenter real world UK experience. Issue 6 (12th May 2021) - Maouche, Nadjoua; Kishore, Bhuvan; Jenner, Matthew W.; Boyd, Kevin; Bhatti, Zara; Bird, Sarah Anne; Chander, Gurvin; Robinson, Rebecca; Vallance, Grant D.; Offer, Mark; Kothari, Jaimal; Peniket, Andy; et al.
Abstract: There are limited real world data on ixazomib, lenalidomide, and dexamethasone (IRd) in multiply relapsed myeloma. We analyzed outcomes of 116 patients who received IRd predominantly at second and subsequent relapse including those refractory to proteasome inhibitors (PIs). With a median follow up 16.3 months, the overall response rate was 66.9%; median progression-free survival (PFS) was 17.7 months with median overall survival (OS) not reached (NR). PFS and OS were significantly shorter in advanced disease (PFS; 12.6 vs. 21.2 months ( p = .01), OS; 15.9 months vs. NR ( p = .01) for ISS3 vs. ISS 1&2, respectively). PFS and OS were significantly shorter in clinical high risk (CHR) compared to standard risk (SR) patients (PFS; 9.3 months vs. NR ( p = .001), OS; 11.5 months vs. NR ( p < .001), respectively). There was a trend toward shorter PFS in PI-refractory patients 13.7 vs. 19.6 months for non-PI refractory ( p = .2). The triplet combination was generally well tolerated.